Avaliação toxicogenetica do biocida timol encapsulado em nanopartícula biogênica de sílica sobre organismos aquáticos - Pereira, Iúri Barbosa (2020)
Introduction: Thymol (Thy) is a monoterpene with biocidal activity against fungi, bacteria, some agricultural pests and mosquito larvae, and other applications. It is repeatedly used in high concentrations, due to its low stability with respect to temperature and light and by its rapid degradation in the environment. These facts can reduce exposure for non-target organisms. The application of nanotechnology by changing the physical-chemical characteristics of Thy and a controlled release system could reduce toxicity as a biocide. Objective: This study aimed to investigate and compare the acute toxicity and genotoxicity of the non-encapsulated Thy and its association in biogenic silica nanoparticles (BSiO2#Thy) on aquatic organisms. Methods: The acute toxicity test was performed with Artemia salina (Meyer et al., 1982 and OECD 202, 2004) and zebrafish (Danio rerio) early-life stage (OECD 236, 2013). The genotoxic effects were investigated in the comet assays with cells from zebrafish larvae (Kosmehl et al., 2006; Tice, 2000). Results: For A. salina test, the acute toxicity of Thy associated in a silica nanoparticle (BSiO2#Thy - LC50-48h = 1.06 ± 0.56 mg/L) remained practically unchanged in comparison to the non-encapsulated Thy (LC50- 48h = 1.03 ± 0.23 mg/L). The unloaded BSiO2 nanoparticle also induced significant mortality, but with less toxic potential (LC50-48h = 61.83 ± 0.43 mg/L). For zebrafish assay, the BSiO2 did not cause significant lethal, sublethal or genotoxic effects, even in high concentrations; however, the BSiO2#Thy was more toxic for the embryo-larval stage of zebrafish (LC50-96h = 13.13 mg/L) when compared to the non-encapsulated Thy (LC50-96h = 25.60 mg/L). In addition, BSiO2#Thy induced the same significant sublethal effects as the non-encapsulated Thy, such as defect in absorption of the yolk sac, pericardial edema and delayed hatching at 96h of exposure. Both formulations (BSiO2#Thy and Thy) were significantly genotoxic from 6.25 mg/L. Conclusion: Therefore, it can be concluded that the encapsulation of the Thy using silica nanoparticles increased acute toxicity for the zebrafish early-life stage and did not remove the toxic potential for A. salina nauplii and genotoxic for zebrafish larvae, since both effects remain unchanged.